Pengaruh Pemahaman Ekonomi Islam, Literasi Keuangan Syariah dan Kecerdasan Emosional Terhadap Perilaku Konsumtif - Elvina Triya Rahmahnusiya; Herlina Yustati; Citra Liza (Universitas Islam Lamongan, 2026)
This study aims to analyze the influence of Islamic economic understanding, Islamic financial literacy, and emotional intelligence on the consumer behavior of Islamic Economics students in Bengkulu City. The method used was a quantitative approach with a causal associative research approach. Data analysis was conducted through validity and reliability tests, classical assumption tests, and multiple linear regression analysis. Hypothesis testing used t-tests, F-tests, and coefficients of determination using SPSS 27 software. The sample size in this study was 95 respondents, with data collected through a Likert-based questionnaire. The results showed that Islamic economic understanding, Islamic financial literacy, and intelligence had a negative and significant effect on consumer behavior. Simultaneously, the three independent variables significantly influenced consumer behavior, contributing 49.6% (R' = 0.496), while the remaining influence was attributed to factors outside the research model.